LSAW attenuation in double-layer-systems - Wallner, Paul; Ruile, Werner; Weigel, Robert (IEEE International Frequency Control Symposium, 1999)
The behavior of Leaky-SAW (LSAW) in layered structures was investigated by new computer calculations. For these investigations rotYX LiTaO3 and rotYX LiNbO3 crystal cuts were used. Surface acoustic wave propagation is strongly influenced by thickness, density, and elasticity of the layers. For LSAW both the velocity and the inherent loss due to bulk wave emission into the substrate depend on these layer properties. Double-layer-systems can be taken into account if Si3N4 or Al2O3 is added on the metal layer. As a result, this double-layer-system shows new properties: the angle of minimum propagation loss and the velocity strongly depend on distinct parameters and ratios of the layers. This means that in double-layer-systems the behavior of LSAW loss and velocity differs from single-layer-structures
elib2cris::1512001600,wallner1999a